Sustainable technique of high density and meadow orcharding for guava - Kumar, Arvind; Pal, Rishi (Indian Horticulture, 2020)
High density planting (HDP) is a modern method of fruit cultivation involving planting of fruit trees densely, allowing smaller dwarf trees with modified canopy for better light interception and distribution, and ease of mechanized field operation. HDP and meadow orcharding gives higher yield as well as returns per unit area by increasing number of trees per unit area. High density and meadow orcharding enhances production and quality of fruits. It is possible to maintain the size and shape of the tree by regular pruning and use of bioregulators.